Belimumab after B cell depletion therapy in patients with systemic lupus erythematosus (BEAT Lupus) protocol: a prospective multicentre, double-blind, randomised, placebo-controlled, 52-week phase II clinical trial - David A Isenberg; Caroline Gordon; Caroline J Dore; Emilia Caverly; Kashfia Chowdhury; Alexis Jones; Patrick Muller; Felicia Ikeji; Michael R Ehrenstein (BMJ Open)
Introduction Few treatment options exist for patients with systemic lupus erythematosus (SLE) who fail conventional therapy. Although widely used to treat lupus, the efficacy of B cell depletion therapy using rituximab has not been demonstrated in randomised clinical trials. Following rituximab, elevated levels of serum B cell activating factor (BAFF) have been associated with failure to remit or subsequent lupus relapse. The administration of belimumab, a monoclonal antibody specific for BAFF and approved for lupus therapy, could potentiate the efficacy of rituximab and enable longer periods of disease remission. The aim of this trial is to assess the safety and efficacy of belimumab following rituximab in patients with SLE.Methods and analysis BEAT Lupus is a double-blind, randomised, placebo controlled, phase II clinical trial. Patients with SLE commencing a treatment cycle of rituximab (two 1g infusions, 2 weeks apart) as standard of care will be randomised to receive belimumab or placebo, 4 to 8 weeks following the first rituximab infusion. Belimumab or placebo infusions are administered for 52 weeks. The primary outcome measure is anti-double stranded DNA (anti-dsDNA) antibody levels at 52 weeks. Secondary outcomes include measures of adverse events, lupus disease activity and cumulative steroid dose. The kinetics of B cell repopulation will be assessed in a subgroup of participants. Belimumab administration after rituximab may provide a novel therapeutic pathway for patients with active lupus if safety is demonstrated in this proof of concept study, and lower anti-dsDNA antibodies levels are achieved in those patients treated with belimumab compared with placebo.Ethics and dissemination The protocol has been reviewed and approved by the Hampstead Research Ethics Committee - London (reference 16/LO/1024). Trial information is available at https://www.isrctn.com/ISRCTN47873003, and the results of this trial will be submitted for publication in relevant peer-reviewed journals. Key findings will also be presented at national and international conferences.Trial registration number ISRCTN47873; date assigned to the registry: 28 November 2016. The stage is pre-results.